2018
DOI: 10.31234/osf.io/kgpvy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Roles of Altruism, Heroism, and Physical Attractiveness in Female Mate Choice

Abstract: The role of prosocial behaviour in female mate choice has been extensively explored, focusing on the desirability of altruism in potential mates, as well as altruism being a mating signal. However, little research has focused on the desirability of heroism and altruism in potential partners. Furthermore, the synergistic effect of attractiveness on the desirability of prosocial traits has only recently been explored, and to our knowledge, has not explored in relation to the desirability of heroism in a romantic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…There is ample evidence to suggest men compete with other men in domains such as altruism and cooperation, to appear to be 'good quality' partners, often trading traits that are of the same 'value', adhering to the laws of supply and demand (see Barclay & Willer, 2006), largely because 'altruists attract' (Farrelly, Lazarus, & Roberts, 2007, p. 327). As such, altruism may have evolved because living cooperatively can increase inclusive fitness through reciprocity (Bhogal, 2019;Farrelly, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is ample evidence to suggest men compete with other men in domains such as altruism and cooperation, to appear to be 'good quality' partners, often trading traits that are of the same 'value', adhering to the laws of supply and demand (see Barclay & Willer, 2006), largely because 'altruists attract' (Farrelly, Lazarus, & Roberts, 2007, p. 327). As such, altruism may have evolved because living cooperatively can increase inclusive fitness through reciprocity (Bhogal, 2019;Farrelly, 2019).…”
mentioning
confidence: 99%
“…Bartlett, & Farrelly, 2019) and trustworthiness(Ehlebracht, Stravrova, Fetchenhauer, & Farrelly, 2018) Margana et al (2019). found that women were attracted to attractive, heroic men more so than attractive, altruistic men.…”
mentioning
confidence: 99%
“…Further evidence of the importance of altruistic behaviour in relationships comes from investigating how we desire such traits in potential partners (Barclay, 2010;Farrelly, 2011Farrelly, , 2013Margana, Bhogal, Bartlett, & Farrelly, 2019;Moore et al, 2013;Oda, Shibata, Kiyonari, Takeda, & Matsumoto-Oda, 2013;Phillips, Barnard, Ferguson, & Reader, 2008). Importantly, a distinction has been observed in terms of length of relationships, with altruism generally being rated more desirable for longer relationships (Barclay, 2010;Bhogal, Galbraith, & Manktelow, n.d.;Farrelly, 2011Farrelly, , 2013.…”
mentioning
confidence: 99%
“…Those that have, have found that individuals display more altruistic behaviors in the presence of potential mating partners (Bhogal, Galbraith & Manktelow, 2016a;Farrelly, Lazarus & Roberts, 2007;Iredale, van Vugt & Dunbar, 2008;Jensen, 2013), and in line with parental investment theory (Trivers, 1972), these displays are stronger in men than women. For example, the synergistic effect of physical attractiveness and different traits of prosociality (heroism and altruism) has been demonstrated in the literature, showing women are attracted to physically attractive men who display prosocial behavior compared to those who do not (Margana, Bhogal, Bartlett, & Farrelly, 2019). This is because as men invest less in reproduction, they have greater variability in reproductive success compared to women and exert more effort into male-male competition (Bateman, 1948).…”
mentioning
confidence: 99%